Synthesis of polymeric composite grafted with mineral particles/graphene oxide-based biomaterial: A promising robust hemostatic bandage. (December 2022) - Ashfaq, Mohammad; Wongpakham, Tepparit; Talreja, Neetu; Chauhan, Divya; Tharasanit, Theerawat; Srituravanich, Werayut
Abstract: The loss of blood is one of the great challenges nowadays, leading to death in many acute circumstances like disasters, militant war, traumatic injury, and surgical procedures requiring newer hemostatic materials. In this aspect, the present study describes the synthesis of inexpensive polymer (polyvinyl alcohol and silk fibroin)-mineral-metal (hydroxyapatite)/carbon (graphene oxide) (PSHG) composite as a hemostatic dressing material for controlling the loss of blood. Initially, silk fibroin (SF), hydroxyapatite (HA), and graphene oxide (GO) were synthesized separately. The esterification of polyvinyl acetate (PVAc) to produce PVA. The mixture of exfoliated GO and HA was mixed at the time of gelation of PVA to produce PVA-HA-GO homogenous solution. The SF solution was mixed into the PVA-HA-GO homogenous solution to produce gray color gel and cast on Petri dishes to produce PSHG biomaterial. The prepared PSHG biomaterials were subjected to biochemical test assays like hemolysis, protein adsorption, platelet aggregation, and blood clotting ability. The PSHG-based biomaterials biocompatibility was ascertained using Human skin fibroblast (HSK) cell lines. The results suggested that the prepared PSHG biomaterial has high absorption ability (∼1040 %), hemolysis (∼2.38 %), platelets aggregation (∼35 %), protein loading (∼30 mg/cm 2 ), and ∼ 89 % blood clot within 15 s. Moreover, PSHG-based biomaterials significantly improved the number of fibroblast cells with high biocompatibility and controlled blood loss. The method synthesizing PSHG-based hemostatic material in the present study is novel, facile, and economically viable. Graphical Abstract: ga1